1998
DOI: 10.1046/j.1365-2141.1998.00624.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum erythropoietin concentration in anaemia of visceral leishmaniasis (kala‐azar) before and during antimonial therapy

Abstract: Summary. Serum erythropoietin (Epo) concentrations and variables of red cell and iron status were studied in 27 Sudanese patients who were treated with sodium stibogluconate for visceral leishmaniasis (kala-azar). Blood haemoglobin increased from 6·4 (Ϯ1·7 SD) to 9·5 (Ϯ1·4) g/dl during treatment. Serum ferritin decreased concomitantly. Serum iron levels were unchanged whereas the total iron binding capacity increased slightly. The pre-treatment serum Epo concentration in relation to the blood haemoglobin conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
3
8
0
Order By: Relevance
“…Regarding the hematological parameters, anemia is a frequent manifestation of visceral leishmaniasis that appear with the disease after an incubation period ranging from one month to several years [47] which is in accordance with our study where anemia was found in mice infected with L. donovani . Cisplatin treatment at both dosages brought about a significant reduction in the white blood cells and anemia.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the hematological parameters, anemia is a frequent manifestation of visceral leishmaniasis that appear with the disease after an incubation period ranging from one month to several years [47] which is in accordance with our study where anemia was found in mice infected with L. donovani . Cisplatin treatment at both dosages brought about a significant reduction in the white blood cells and anemia.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, we documented that severe CVL is associated with a disorder in the erythroid bone marrow compartment, with significantly decreased red blood cell counts and hemoglobin and hematocrit values in symptomatic dogs, corroborating previous studies and elucidating the genesis of anemia in active CVL. It is possible that anemia could be related to factors such as formation of colonies impaired and increased hemolysis in enlarged spleen and liver associated with an inflammatory response to L. infantum infection [27]. In addition, a reduced plasma iron in the presence of greatly increased iron stores suggested that reticuloendothelial hyperplasia was accompanied by abnormal iron retention by macrophages typical of the anemia of chronic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Anaemia is a side effect of many drugs [], some interfering at medullary red cell maturation and others inducing extracorpuscular, immunological damage to the red cells []. Finally drug‐induced anaemia may proceed through inhibition of Epo synthesis, as seen with sodium‐stibogluconate used to treat visceral leishmaniasis [].…”
Section: Discussionmentioning
confidence: 99%